Analisis Pengaruh Kualitas Pelayanan terhadap Kepuasan Konsumen Mutiara Salon Wanita Jatibening Pondok Gede Tahun 2024 - Feri Ragil Saputra; Moh Taufan Nugroho (Institut Teknologi dan Bisnis (ITB) Semarang, 2024)
This research aims to examine the influence of service quality on consumer satisfaction at Mutiara Women's Salon Jatibening Pondok Gede in 2024. To obtain data, the Service Quality and Consumer Satisfaction instrument in the form of a questionnaire (Questionnaire) was used. The research method used is quantitative with an associative approach. The sample in this study was 78 respondents. The analysis technique used is simple linear regression which is processed using the SPSS program. Based on the results of data analysis in the regression equation model, it is known that the results of the analysis of the coefficient of determination test in the Mode Summary table, obtained an R Square value (coefficient of determination) of 0.450, which means that the influence of the independent variable (X) on the dependent variable (Y) is 45%. So it can be concluded that the Service Quality variable has an influence of 45% on the Consumer Satisfaction variable. And another 55% was influenced by other variables not examined in this study.